A QUICK METHOD OF SEGMENT AND LINE DRAWING ON THE SCREEN BASED ON CONTINUOUS FRACTION ALGORITHM - Borodin, Viktor A. (Proceedings of National Aviation University (archive), 2009)
In the paper a quick method for segment and line drawing on the screen is proposed. This method is proposed for using in interactive aviation complexes. The method is grounded on the algorithm of continuous fraction and uses half as many operations comparing to classical methods.